Desarrollo de un modelo de gestión de producción que permita estandarizar los procesos operativos en taller industrial Tinoco para mejorar la productividad - Loor Mendoza, Anthony Juvencio (2022)
The present investigation is focused on the Development of a Production Management Model that allows standardizing the operational processes in TALLER INDUSTRIAL TINOCO with the objective of increasing the efficiency in the production process of industrial tools (agricultural machinery) and identifying the consumption of resources that impede the development of production processes. Through direct observation, it was possible to recognize that there is a deficiency in the organization of the activities, which generates instability in the development of the processes, giving rise to an accumulation of work, in turn generating a delay in the deadlines. delivery. The company does not have a planning that allows it to have control of the activities that take place in it. Therefore, operating times were standardized in order to have a foundation for the organization and control of tasks for each worker. For this reason, the need arises to make a proposal for improvement in its production process, which reduces the delivery time (lead time) of the product to its customers. The present investigation is focused on the Development of a Production Management Model that allows standardizing the operational processes in TALLER INDUSTRIAL TINOCO with the objective of increasing the efficiency in the production process of industrial tools (agricultural machinery) and identifying the consumption of resources that impede the development of production processes. Through direct observation, it was possible to recognize that there is a deficiency in the organization of the activities, which generates instability in the development of the processes, giving rise to an accumulation of work, in turn generating a delay in the deadlines. delivery. The company does not have a planning that allows it to have control of the activities that take place in it. Therefore, operating times were standardized in order to have a foundation for the organization and control of tasks for each worker. For this reason, the need arises to make a proposal for improvement in its production process, which reduces the delivery time (lead time) of the product to its customers. Key words: management, production, improvement, productivity.